Eucalyptus Globulus protects against diclofenac sodium induced hepatorenal and testicular toxicity in male rats - Ahmed Abdelmoniem Mousa; Ahmed Essam Elweza; Hamed Talaat Elbaz; Enas Abd El-aziz Tahoun; Khaled Mohamed Shoghy; Islam Elsayed; El Barbary Hassan (Journal of Traditional and Complementary Medicine, 2020)
The current study was conducted to investigate the protective properties of Eucalyptus globulus leaves methanolic extract (EGLME) against diclofenac sodium (DS) induced hepatorenal and testicular toxicity in male rats. A total of 40 rats were equally divided into 4 groups, Control, Diclofenac sodium (DS), EGLME and DS + EGLME groups, respectively. DS and EGLME were administered orally at dose rate 2.5 and 100 mg/kg BW, 4 times/week for 8 weeks, respectively. Administration of DS distorted hepatorenal functions manifested by alteration of serum levels of ALT, AST, total protein and albumin, creatinine and urea with changes of histological architectures. DS caused reproductive toxicity represented by minimized sperm count, individual sperm motility and viability; depleted concentration of reduced glutathione (GSH) in testicular tissue; and decreased testosterone level with alteration in testicular histological features. In contrast, co-treatment of DS intoxicated rats with EGLME protected rats against the adverse effects of DS revealing enhancing properties of EGLME on rats’ liver, kidney and testes. In conclusion, we demonstrated that EGLME had a potent protecting property against DS induced hepatic, renal and testicular toxicity in male rats, with special concern to testicular tissue via modulation of GSH as an oxidant marker. Taxonomy: (classification by EVISE): Diclofenac sodium toxicity (hepatorenal and testicular toxicity), co-treatment with natural herbal extract, blood biochemical assays, tissue anti-oxidants assay, histopathology and reproductive indices analyses.